Current Practice of Heart Donor Evaluation in Germany: Multivariable Risk Factor Analysis Confirms Practicability of Guidelines. (30th September 2013) - Zeissig, Sylke Ruth; Fischer-Froehlich, Carl-Ludwig; Polster, Frank; Fruehauf, Nils R.; Kirste, Guenter; Schmidtmann, Irene
Abstract : Background . Organ shortage has liberalised the acceptance criteria of grafts for heart transplantation, but which donor characteristics ultimately influence the decision to perform transplantation? For the first time this was evaluated using real-time donor data from the German organ procurement organization (DSO). Observed associations are discussed with regard to international recommendations and guidelines. Methods . 5291 German donors (2006–2010) were formally eligible for heart donation. In logistic regression models 160 donor parameters were evaluated to assess their influence on using grafts for transplantation (random split of cases: 2/3 study sample, 1/3 validation sample). Results . Successful procurement was determined by low donor age (OR 0.87 per year; 95% CI [0.85–0.89], P < 0.0001 ), large donor height (OR 1.04 per cm; 95% CI [1.02–1.06], P < 0.0001 ), exclusion of impaired left ventricular function or wall motion (OR 0.01; 95% CI [0.002–0.036], P < 0.0001 ), arrhythmia (OR 0.05; 95% CI [0.009–0.260], P = 0.0004 ), and of severe coronary artery disease (OR 0.003; 95% CI [<0.001–0.01], P < 0.0001 ). Donor characteristics differed between cases where the procedure was aborted without and with allocation initiated via Eurotransplant.